Initial Experience With a New Intraoral Midface Distraction Device - Burstein, Fernando (J Craniofac Surg, 2015)
Maxillary hypoplasia that necessitates surgical advancement affects approximately 25% of patients born with cleft lip and palate. Syndromic conditions such as Crouzon may also be accompanied by significant maxillary hypoplasia. Severe maxillary hypoplasia can result in airway obstruction, malocclusion, proptosis, and facial disfigurement. For optimal stability, severe hypoplasia is best addressed with maxillary distraction osteogenesis. Twenty-two patients (15 boys, 7 girls, ages 6–16 years, mean age 10 years) with severe midface hypoplasia underwent midface distraction with new internal maxillary distraction (IMD) device at our institution. Total distraction distances ranged from 15 to 30 mm. There were no major complications, and all of them had improvement in functional and aesthetic parameters. There were 2 minor complications and 2 patients failed to distract the full distance because of converging vectors. Early maxillary distraction in patients with severe midface hypoplasia is a useful technique to provide interval correction of severe maxillary hypoplasia before skeletal maturity and definitive orthognathic surgery is contemplated, and it is a good tool to improve occlusion, aesthetics, and self-perception in younger patients.